ENDODONTIC “TRENDS”: WHAT DOES SCIENCE HAVE TO SAY ABOUT THEM? - Silva, Emmanuel J.N.L. (Revista Científica do CRO-RJ (Rio de Janeiro Dental Journal), 2020)
The Endodontic world is often flooded with new products and protocols, generally with a strong commercial appeal, ensuring improvements in the outcomes of root canal treatment. These new techniques have often been labeled as being less invasive or more biology-reliant and have been indicated to replace scientifically and clinically supported therapies. The most recent and widely discussed examples in the endodontic scenario are the minimally invasive treatments (especially minimally invasive endodontic access cavities), the so-called “natural” disinfection therapies such as ozone therapy, and new “biological miraculous” root canal sealers.